KAJIAN RELASI GENDER DALAM PENGHIDUPAN KELUARGA NELAYAN DI KAMPUNG TELUK SULAIMAN KECAMATAN BIDUK-BIDUK KABUPATEN BERAU - Risqi Wiqanda P; Erwiantono; Fitriyana (Jurnal Pembangunan Perikanan dan Agribisnis, 2021)
This study aimed at knowing the family perception toward the concept of gender relation, knowing the pattern of job distribution, contribution of income, the pattern of decision-making, working time duration, and the role in the access and control. The sampling method was purposive sampling method with a total sample of 15 fishermen families (husbands and wives). The method for data analysis in this study was crossed tabulation-based method and business analysis. The results of this study: The gender perception that was the husband and wife realized that there should be no conflict over gender differences in supporting the family financially, yet they should support and complete each other. Hence, it can be concluded that fishermen families are at the Social exchange theory. The pattern of job distribution was that the domestic activities were mostly performed by the wives, while public activities were performed by the husbands. The contribution to income in the family was that the average income of husbands per year was more than the average income of wives, namely 82% and 18% consecutively. Decision-making related to domestic activities was dominantly performed together, by both husband and wife. Meanwhile of public activities was dominated by the husband.The average working time duration for the wife was 5.9 hours/day (24.7%) dan work time of husband was 12.2 hours/day (50.7%) on average. The access to resources, could be accessed jointly by husband and wife. For control, there were various dominations.